Image quality in digital radiographic systems - Almeida Solange Maria de; Oliveira Ana Emília Figueiredo de; Ferreira Rívea Inês; Bóscolo Frab Norberto (Fundação Odontológica de Ribeirão Preto, 2003)
The aim of the present study was to evaluate the image quality of four direct digital radiographic systems. Radiographs were made of the maxillary central incisor and mandibular left molar regions of a dry skull, and an aluminum step-wedge. The X-ray generator operated at 10 mA, 60 and 70 kVp, and images were acquired with 3, 5, 8, 12, 24 and 48 exposure pulses. Six well-trained observers classified the images by means of scores from 1 to 3. Collected data were submitted to nonparametric statistical analysis using Fisher's exact test. Statistical analysis showed significant differences (p<0.01) in image quality with the four systems. Based on the results, it was possible to conclude that: 1) all of the digital systems presented good performance in producing acceptable images for diagnosis, if the exposures of the step-wedge and the maxillary central incisor region were made at 5 pulses, as well as at 8 pulses for the mandibular left molar region, selecting 60 or 70kVp; 2) higher percentages of acceptable images were obtained with the administration of lower radiation doses in CCD-sensors (charge-coupled device); 3) the Storage Phosphor systems produced acceptable images at a large range of exposure settings, that included low, intermediate and high radiation doses.